2014
DOI: 10.1371/journal.pone.0104421
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, Social Integration and Consumption of Sugar-Containing Beverages: Testing the Social Baseline Theory

Abstract: ObjectiveSocial Baseline Theory (SBT) proposes that close relationships aid in metabolic resource management and that individuals without significant relationships may experience more demands on their own neural metabolic resources on a daily basis when solving problems, remaining vigilant against potential threats and regulating emotional responses. This study tests a hypothesised consequence derived from SBT: relative social isolation leads to increased levels of sugar intake.MethodsBased on cross-sectional,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 44 publications
4
57
0
Order By: Relevance
“…to homes ("attachhome"; Harris et al, 1996), daily sugary drinks consumption ("gluctot"; Henriksen et al, 2014) and diet drinks consumption ("artgluctot"; Henriksen et al, 2014), known benchmarks of CBT, like sex ("sex"), height ("height"), weight ("weightkg"), and whether they used medication ("meds"; Bergmann, 1847;Hill & Rahimtulla, 1965;Peters, 1986).…”
Section: Methods Pilot Studymentioning
confidence: 99%
See 2 more Smart Citations
“…to homes ("attachhome"; Harris et al, 1996), daily sugary drinks consumption ("gluctot"; Henriksen et al, 2014) and diet drinks consumption ("artgluctot"; Henriksen et al, 2014), known benchmarks of CBT, like sex ("sex"), height ("height"), weight ("weightkg"), and whether they used medication ("meds"; Bergmann, 1847;Hill & Rahimtulla, 1965;Peters, 1986).…”
Section: Methods Pilot Studymentioning
confidence: 99%
“…We measured a number of known correlates of core body temperature using a questionnaire and a number of social relationship variables that -based on prior research -should logically be related to core body temperature (e.g., nostalgia (Zhou et al, 2012) or attachment to homes (Van Acker et al, 2016)). We included a number of variables that have been found to relate to body temperature (stress; Marazziti et al, 1992; whether participants use medication) or those that have been known to relate to environmental temperature variations (nostalgia; Zhou et al, 2012;attachment to homes;Van Acker et al, 2016) or to metabolism and social network quality (like daily diet/sugary drinks consumption; Henriksen et al, 2014).…”
Section: The Human Penguin Project Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, evidence suggests that hills literally appear less steep when standing next to a friend [14]. Moreover, socially isolated individuals consume more sugar, even after adjusting for body mass index, weight related self-image, depression, physical activity, educational level, age and income [15]. To the human brain, social and metabolic resources are treated almost interchangeably.…”
Section: Social Relationships Decrease the Predicted Cost Of The Envimentioning
confidence: 99%
“…There are some other studies that were documented on the role of skin-to-skin contact and its relation to skin temperature which may show the connection between touch and skin temperature, to which we return when we discuss developmental thermoregulation. More indirect links have been provided between close relationships and the regulation of metabolic resources: Henriksen et al (2014) found that being socially integrated is related to a lesser consumption of drinks containing sugar during pregnancy, while thinking about a romantic partner (who is likely to be a source of warmth) 11 Evidence on huddling strategies was cited by Ebensperger (2001) on Bathyergidae (Heterocephalus glaber- Withers and Jarvis, 1980), Muridae (Abrothrix andinus, Abrothrix lanosus- Canals et al, 1997;Apodemus agrarius-Tertil, 1972; Apodemus flavicollis -Fedyk, 1971; Clethrionomys glareolus -Górecki, 1968;Gebczyński, 1969;Gebczyńska and Gebczyński, 1971; Eligmodontia typus- Canals et al, 1997;Meriones unguiculatus-Contreras, 1984;Mus musculus-Prychodko, 1958;Martin et al, 1980;Contreras, 1984;Microtus townsendii-Andrews et al, 1987;Ochrotomys nuttalli-Springer et al, 1981;Ondatra zibethicus-Bazin and MacArthur, 1992; Peromyscus leucopus- Glaser and Lustick, 1975;Vogt and Lynch, 1982; Peromyscus maniculatus- Andrews and Belknap, 1986;Phyllotis darwini-Canals et al, 1997;and Reithrodontomys megalotis-Pearson, 1960), Myocastoridae (Myocastor coypus- Moinard et al, 1992), Octodontidae (Octodon degus- Canals et al, 1989), and Sciuridae (Ammospermophilus leucurus- Karasov, 1983; Glaucomys volans- Stapp et al, 1991), but also for round-tailed ground squirrels Spermophilus tereticaudus (Dunford, 1977), southern flying squirrels Glaucomys volans (Stapp et al, 1991;Layne and Raymond, 1994), gray squirrels …”
Section: Communal Ways To Thermoregulate Sociallymentioning
confidence: 99%